Where the Wild Things Are: Transposable Elements as Drivers of Structural and Functional Variations in the Wheat Genome - Bariah, Inbar; Keidar-Friedman, Danielle; Kashkush, Khalil (Frontiers in Plant Science, 2020)
Transposable elements (TEs) are major contributors to genome plasticity and thus are likely to have a dramatic impact on genetic diversity and speciation. Recent technological developments facilitated the sequencing and assembly of the wheat genome, opening the gate for whole genome analysis of TEs in wheat, which occupy over 80% of the genome. Questions that have been long unanswered regarding TE dynamics throughout the evolution of wheat, are now being addressed more easily, while new questions are rising. In this review, we discuss recent advances in the field of TE dynamics in wheat and possible future directions.